Effect of Thyroxine Therapy on Depressive Symptoms Among Women With Subclinical Hypothyroidism. Issue 4 (April 2020) - Costantine, Maged M.; Smith, Karen; Thom, Elizabeth A.; Casey, Brian M.; Peaceman, Alan M.; Varner, Michael W.; Sorokin, Yoram; Reddy, Uma M.; Wapner, Ronald J.; Boggess, Kim; Tita, Alan T.N.; Rouse, Dwight J.; et al.
Abstract : OBJECTIVE: To estimate the effect of antenatal treatment of subclinical hypothyroidism on maternal depressive symptoms. METHODS: We conducted an ancillary study to a multicenter trial in women with singleton pregnancies diagnosed with subclinical hypothyroidism randomized to antenatal thyroxine therapy or placebo. Treatment was discontinued at the end of pregnancy. Women with overt thyroid disease, diabetes, autoimmune disease, and those diagnosed with depression were excluded. Participants were assessed for depressive symptoms using the Center for Epidemiological Studies-Depression scale (CES-D) before starting the study drug (between 11 and 20 weeks of gestation), between 32 and 38 weeks of gestation, and at 1 year postpartum. The primary outcome was maternal depressive symptoms score as assessed using the CES-D. Secondary outcome was the percentage of women who scored 16 or higher on the CES-D, as such a score is considered screen-positive for depression. RESULTS: Two hundred forty-five (36.2% of parent trial) women with subclinical hypothyroidism were allocated to thyroxine (n=124) or placebo (n=121). Median CES-D scores and the proportion of participants with positive scores were similar at baseline between the two groups. Treatment with thyroxine was not associated with differences in CES-D scores (10 [5–15] vs 10 [5–17]; P =.46) or in odds of screening positive in the third trimester compared with placebo, even after adjusting for baseline scores (24.3% vs 30.1%, adjusted odds ratio 0.63, 95% CI 0.31–1.28, P =.20). At 1 year postpartum, CES-D scores were not different (6 [3–11] vs 6 [3–12]; P =.79), nor was the frequency of screen-positive CES-D scores in the treated compared with the placebo group (9.7% vs 15.8%; P =.19). Treatment with thyroxine during pregnancy was also not associated with differences in odds of screening positive at the postpartum visit compared with placebo even after adjusting for baseline scores. Sensitivity analysis including women who were diagnosed with depression by the postpartum visit did not change the results. CONCLUSIONS: This study did not achieve its planned sample size, thus our conclusions may be limited, but in this cohort of pregnant women with subclinical hypothyroidism, antenatal thyroxine replacement did not improve maternal depressive symptoms. Abstract : Antenatal thyroxine replacement did not improve depressive symptoms in a cohort of pregnant women with subclinical hypothyroidism.